2017
DOI: 10.4172/2157-7110.1000165
|View full text |Cite
|
Sign up to set email alerts
|

Textural and Microbiological Qualities of Vegetable Soybean (Edamame) Affected by Blanching and Storage Conditions

Abstract: Vegetable soybean (edamame) is a highly perishable product. Blanching combined with cold storage is an excellent preservation method to extend edamame shelf-life. The effects of different blanching and storage conditions on textural and microbiological qualities of in-pod edamame were investigated. Blanching for 2.5 min or longer at 100°C water reduced peroxidase activity by over 98%. The thermal denaturation temperature of edamame beans increased 30ºC by blanching. The durations of blanching and refrigerated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 24 publications
2
20
1
Order By: Relevance
“…Pao et al (2008) investigated the effect of frozen edamame on its microbiological quality and indicated that blanching treatment at 98°C for about 60 s eliminates yeasts, molds, coliforms as well as infectious species Escherichia coli and Listeria spp. Moreover, Xu et al (2012) demonstrated that blanching for 2.5 min or more at 100°C increases the green color intensity of edamame beans, Source: Chadha and Oluoch (2004). reduces the activities of yeasts, molds, total bacteria and 98% of peroxidase activities, thus alleviating the toxic effect of peroxide accumulation. Steam blanching of fresh pods has also been reported to retain more soluble sugars in edamame than the storage of edamame pods in open air at 25°C for 8 to 12 days found to be responsible for quick decrease in sucrose content causing the loss of sweet taste (Saldivar et al, 2010;Mozzoni et al, 2009).…”
Section: Harvest and Post-harvest Handlingmentioning
confidence: 99%
See 1 more Smart Citation
“…Pao et al (2008) investigated the effect of frozen edamame on its microbiological quality and indicated that blanching treatment at 98°C for about 60 s eliminates yeasts, molds, coliforms as well as infectious species Escherichia coli and Listeria spp. Moreover, Xu et al (2012) demonstrated that blanching for 2.5 min or more at 100°C increases the green color intensity of edamame beans, Source: Chadha and Oluoch (2004). reduces the activities of yeasts, molds, total bacteria and 98% of peroxidase activities, thus alleviating the toxic effect of peroxide accumulation. Steam blanching of fresh pods has also been reported to retain more soluble sugars in edamame than the storage of edamame pods in open air at 25°C for 8 to 12 days found to be responsible for quick decrease in sucrose content causing the loss of sweet taste (Saldivar et al, 2010;Mozzoni et al, 2009).…”
Section: Harvest and Post-harvest Handlingmentioning
confidence: 99%
“…Preference analysis, nutritional and anti-nutritional evaluation of edamame varieties were also reported by various authors (Wszelaki et al, 2005;Bhattacharya and Malleshi, 2012;Carson et al, 2011;Carson et al, 2012;Castoldi et al, 2011;Jadhav et al, 2018;Mohamed and Rangappa, 1992;Takahashi and Ohyama, 2011). Furthermore, storage of edamame was also investigated (Saldivar et al, 2010;Xu et al, 2012;Lara et al, 2019). Genetic diversity was assessed with nutritional, morphological and molecular markers (Mimura et al, 2007;Dong et al, 2014;Ramya and Mummigatti, 2015;Williams, 2015;Pooprompan et al, 2006;Jadhav et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Color of raw and cooked edamame was measured with a Minolta CR-400/410 chroma meter (Konica Minolta Camera Co., Ltd., Osaka, Japan) to determine 'L*' (lightness) from black (0) to white (100), 'a*' [red (?a) to green (-a) color], and 'b*' [yellow (?b) to blue (-b) color]. Intensity of green color was calculated as -a*/b* [20].…”
Section: Physicochemical Propertiesmentioning
confidence: 99%
“…The protein content in edamame is up to 40% with fat (without cholesterol) in the amount of 20%, carbohydrate 33% and fiber 6% [10]. On the other hand, edamame is also rich in vitamins and minerals [11]. Protein is one of the prominent components in edamame.…”
Section: Introductionmentioning
confidence: 99%